1997
DOI: 10.1097/00000539-199706000-00034
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sevoflurane Anesthesia on Insulin Secretion and Glucose Metabolism in Pigs

Abstract: We investigated the effects of two different concentrations of sevoflurane, 0.4 minimum alveolar anesthetic concentration (MAC) and 1.0 MAC, on insulin secretion before, during, and after sevoflurane anesthesia using three successive intravenous glucose tolerance tests (IVGTT) in pigs with indwelling catheters. We also investigated changes in the levels of plasma glucose, catecholamines (epinephrine [E], norepinephrine [NE]), and cortisol (Cor). The pigs were grouped as awake, 0.4 MAC, or 1.0 MAC. Sevoflurane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 16 publications
3
25
0
1
Order By: Relevance
“…The differences may be from different species, anesthesia doses, or duration. Enflurane [25], isoflurane [26], and sevoflurane [27] may impair glucose tolerance by decreasing insulin secretion and glucose utilization [28], and activating of K-ATP channels [29], [30]. Moreover, this effect of isoflurane or sevoflurane on blood glucose was equal, and did not vary as altering inhaled concentration [31].…”
Section: Discussionmentioning
confidence: 99%
“…The differences may be from different species, anesthesia doses, or duration. Enflurane [25], isoflurane [26], and sevoflurane [27] may impair glucose tolerance by decreasing insulin secretion and glucose utilization [28], and activating of K-ATP channels [29], [30]. Moreover, this effect of isoflurane or sevoflurane on blood glucose was equal, and did not vary as altering inhaled concentration [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane, one of the volatile inhaled anesthetics, was used in the present study, and our results may have been affected by alteration of a neuroendocrine stress response caused by inhaled anesthesia. A previous study demonstrated that sevoflurane did not stimulate catecholamine (epinephrine and norepinephrine) or cortisol secretion and significantly inhib- ited basal and glucose-stimulated insulin secretion in pigs (32). In addition, pentobarbital significantly increased plasma insulin concentration, while sevoflurane did not increase it, in fed rats (33).…”
Section: Discussionmentioning
confidence: 92%
“…Volatile anesthetics, such as sevoflurane, attenuate insulin secretion by activating Table 6. Changes in blood glucose levels during insulin tolerance tests in groups S-ITT, SL-ITT, and P-ITT adenosine triphosphate-sensitive potassium channels in β-islet cells (2)(3)(4)(5). We previously found that propofol anesthesia enhances insulin secretion in rats (6,7).…”
Section: Discussionmentioning
confidence: 94%
“…Volatile anesthetics, such as sevoflurane, activate adenosine triphosphatesensitive potassium channels in β-islet cells, resulting in attenuated insulin secretion (2)(3)(4)(5). Although the precise mechanisms have not been elucidated, insulin secretion is significantly enhanced in rats under propofol anesthesia (6,7).…”
Section: Introductionmentioning
confidence: 99%